2022
DOI: 10.1007/s40615-022-01396-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Predict HPV Vaccination Behavior Among Young Men-Who-Have-Sex-with-Men in the Greater Philadelphia Region

Abstract: Human papillomavirus (HPV) is one of the most common sexually transmitted infections in the USA. HPV is acknowledged as one of the leading causes of anal cancer, with an increased risk in men who have sex with men (MSM), when compared to age-matched heterosexual men. This study highlights the various factors that influence and impede HPV vaccination uptake among a multiracial cohort of young-MSM (YMSM). A total of 444 participants aged 18 to 27 in the Greater Philadelphia region completed an online survey. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The higher vaccine adherence in the Tel Aviv district was reflected in other studies showing higher HPV vaccination and healthcare utilization in other metropolitan areas 14 . For example, a study showed HPV vaccine adherence among MSM to be 83% when vaccination was recommended by a healthcare provider, compared with only 5% when no such recommendation was precised 8,9,15 . The main Israel LGBT clinics are located in the Tel Aviv district and, to our knowledge, were more likely to recommend the MVA vaccine to their patients.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The higher vaccine adherence in the Tel Aviv district was reflected in other studies showing higher HPV vaccination and healthcare utilization in other metropolitan areas 14 . For example, a study showed HPV vaccine adherence among MSM to be 83% when vaccination was recommended by a healthcare provider, compared with only 5% when no such recommendation was precised 8,9,15 . The main Israel LGBT clinics are located in the Tel Aviv district and, to our knowledge, were more likely to recommend the MVA vaccine to their patients.…”
Section: Discussionmentioning
confidence: 52%
“…14 For example, a study showed HPV vaccine adherence among MSM to be 83% when vaccination was recommended by a healthcare provider, compared with only 5% when no such recommendation was precised. 8,9,15 The main Israel LGBT clinics are located in the Tel Aviv district and, to our knowledge, were more likely to recommend the MVA vaccine to their patients.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, a comprehensive analysis of the factors associated with HPV vaccination intention among the MSM population is vital to increase HPV vaccination coverage among the MSM population. Previous studies have used logistic regression based on independent conditions to explore factors associated with vaccination intention and have used odds ratios (ORs) to reflect the degree of association [ 21 , 22 , 23 ]. In reality, factors are often interdependent, and relationships may have a complex network structure.…”
Section: Introductionmentioning
confidence: 99%